Frequency of Different Etiologies for Anaemia in Anaemic Children Reporting to Combined Military Hospital, Abbottabad - Ramzan, Amna; Iqbal, Amjad; Shahzad, Sohail; Zaidi, Syed Taqi Hasan; Nazar , Maira (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the frequency of different etiologies for anaemia in anaemic children reporting to Combined Military Hospital, Abbottabad. Study Design: Cross- sectional study. Place and Duration of Study: Department of Paediatrics, Combined Military Hospital Abbottabad, Pakistan from Jan 2022 to May 2024. Methodology: A total of 181 children with ages between two and twelve years with haemoglobin <11.0g/dL were studied. Patients who received a blood transfusion, surgery or trauma within the past three months or who did not complete workup to determine etiological cause for anaemia/were lost to follow-up, or had received treatment prior to presentation for anaemia were excluded. Blood and other samples (where required) were collected from each child and analyzed in the hospital laboratory. Ancillary tests such as haemoglobin electrophoresis, stool/urine examination, bone marrow aspiration and trephine sampling and endoscopic examinations were performed as, and when, needed. Results: The median age of the children was 6.00(5.00) years, with 102(56.4%) cases being male. Dietary iron deficiency anaemia was seen in 89(49.2%) cases. Malabsorption-associated mixed deficiency, dietary mixed deficiency and isolated vitamin B12 deficiency occurred in 24(13.3%), 17(9.4%), and 16(8.8%) cases, respectively. Other causes included β-thalassemia trait, IDA secondary to worm infestation, isolated folic acid deficiency and IDA secondary to menorrhagia which were seen in 10 (5.5%), 9(5.0%), 8(4.4%) and 5(2.8%) cases, respectively. Conclusion: Iron deficiency anaemia is the most common cause of deficiency in children in Abbottabad.